Z dziejów polsko-włoskich relacji XIX wieku. Kultura, militaria, społeczności. Szkice polityczno-historyczne .......... 79 - Beroud, Magdalena (Riflessioni intorno alla storia politica d’Italia = Refleksje wokół historii politycznej Włoch, 2025)
FROM THE HISTORY OF POLISH-ITALIAN RELATIONS IN THE 19TH CENTURY: CULTURE, MILITARY, COMMUNITIES. POLITICAL AND HISTORICAL SKETCHESThroughout almost the entire 19th century, numerous Polish volunteers participated in the struggle for independence and unification of Italy. On the other hand, Italian volunteers took part in the Polish independence uprisings. Their greatest contribution to the Polish armed effort, it should be emphasized, took place during the Spring of Nations and the January Uprising. It is also important to remember the organizational opportunities created by Italians for the Polish insurgents, providing refuge assistance and training opportunities for emigrants, enhancing their combat skills, as exemplified by the famous school in Cuneo. The latter school trained personnel for the future insurgent forces of the January Uprising of 1863. The author discusses these events and Polish-Italian military cooperation, perceiving them as the foundation for the current good relations between Warsaw and Rome.